From silenced to vocal: Teacher unionists' growing influence on educational development in Taiwan. (November 2019) - Hung, Cheng-Yu
Highlights: The teachers' unions in Taiwan have positioned professional development as the overarching goal in the micro-politics of the organisation. The unions aim to consolidate its status through the establishment of a self-disciplinary and consultancy system. The corporatist model reminds the unions to take the initiative to reach the 'peak associations' rank and enter the centre of power. The unions have built allies across the ruling and opposition parties and have plunged into the political sphere to struggle for power. Micro- and macro-political strategies shuttle back and forth between professionalism and unionism aiming to elevate the status of unions. Abstract: The oldest teachers' union in Taiwan, The National Federation of Teachers Unions, has been in operation for almost eight years. This is in stark contrast with the situation in Western countries where teachers' unions have existed for over a century. This article looks into how these pioneering teacher unionists emulated their western forerunners and finally formed a new voice for their peers. By means of interviews with twenty founding members, it is proposed that unionism and professionalism are not mutually exclusive and that the betterment of working conditions can contribute to the quality of education delivered to children. In line with this integrated philosophy, the unions have developed strategies to exercise their right to speak. Micro-strategies champion professional identity to improve members' teaching practice and gain the public's trust. Macro-strategies involve teacher unionists' activism in power politics, contrary to the traditional Confucian image of teachers in Taiwan. The evolution of teacher unionism in such a young democracy can provide inspiration to nearby countries with educators still silenced by those in power and show that teachers can play an active role in transforming education outside the classroom.